AB0660 Predictors of Flare after Tapering Anti-TNF Therapy in Patients with Axial Spondyloarthritis. (15th July 2016) - Monjo Henry, I.; Plasencia, C.; Navarro-Compán, V.; Paredes, B.; Bonilla, G.; Nuño, L.; Peiteado, D.; Villalba, A.; Pascual-Salcedo, D.; Ramiro, S.; de Miguel, E.; Martín-Mola, E.; et al.
Abstract : Background: In most patients with axial spondyloarthritis (axSpA) achieving a clinical response after receiving standard dose of anti-TNF therapy, it seems possible to decrease anti-TNF dose without leading to flare of the disease. However, a minority of patients fails to this strategy and need to maintain standard dose of anti-TNF therapy in order to keep disease activity under control. Objectives: To identify prognostic factors of flare after tapering anti-TNF therapy in patients with axSpA who achieve sustained clinical response with standard dose of this therapy. Methods: This was a restrospective, observational study performed in a tertiary hospital. All patients with axSpA who had achieved sustained low disease activity for at least 6 months after receiving standard dose of a first anti-TNF drug and who had later decreased the dose of anti-TNF therapy were included. Low disease activity was defined as BASDAI <4 plus normal value of CRP. All patients were followed-up during 2 years after starting on tapering strategy. Collected data included: demographic (age, gender) and disease characteristics (HLA-B27, disease duration, peripheral involvement), smoking status, clinical disease activity measures (BASDAI, ASDAS, CRP) before starting and before decreasing anti-TNF therapy, time under anti-TNF therapy, concomitant treatment, and time in remission before tapering. Patients were followed-up during 2 years after tapering anti-TNF therapy. Flare was defined as BASDAI ≥4 plus elevated CRP (>5mg/L) and/or delta-BASDAI ≥2. To identify possible predictors of flare, univariable and multivariable logistic regression analyses were employed including all variables described within the collected data as independent factors. Results: Fifty-three patients with axSpA receiving a tapering strategy after achieving low disease activity were included. Characteristics for these patients are presented in table 1 . Four patients interrupted anti-TNF due to adverse effect before ending the study. In total, 8/49 patients (16%) had a flare during the 2-year follow-up period. In the univaribale analysis, only the age (OR=1.06; p=0.05), BASDAI before tapering (OR=2.64; p=0.01) and ASDAS before tapering (OR=4.12; p=0.08) were significantly associated with the occurrence of flare. In the multivariable analysis, only the BASDAI before tapering remained statistically significantly associated with flare (OR=2.39; p=0.03). Conclusions: In patients with axSpA and sustained clinical response to anti-TNF therapy, a tapering strategy leads to flare in less than 20% of patients. The value of BASDAI before tapering anti-TNF therapy predicts the occurrence of flare. This may help us to select the appropriate patients and moment to implement a tapering strategy in patients with axSpA. Disclosure of Interest: None declared